Extracellular calcium signaling - Hofer, Aldebaran M. (Henry Stewart Talks, 2012)
Local accumulations and depletions of extracellular Calcium, Systemic Calcium homeostasis, Extracellular Ca2+ sensing receptor (CaR), Mutations in the human CaR, How and when Calcium fluctuates locally, Calcium fluxes across the plasma membrane during calcium signals can be significant, Oscillations in external Calcium, Ca2+ selective microelectrodes, The effect of Carbachol, Ways in which local [Ca2+]out can change, Extracellular Ca2+ "sensors", Ca2+ as a paracrine messenger, Ca2+ as a local extracellular messenger, Co-culture model system, Ca2+ as an autocrine signaling molecule, Evidence for the physiological importance of fluctuations in [Ca2+]out, [Ca2+]out affects alkaline secretion
Reviewed at 2020/08/12